How to Boost the Impact of Intra-African Trade on Income in Africa ? - (:unkn) unknown (My University, 2019)
Regional trade integration is viewed by both international institutions and local political leaders as a key tool for promoting inclusive growth and reducing poverty in Africa. However, several structural weaknesses in African economies undermine trade integration and inhibit its income-enhancing effect. This paper aims to study the conditional effects of intra-African trade openness on the standard of living in Africa by highlighting the influence of these structural weaknesses. Our results clearly show that the impact of intra-regional trade on income depends on the diversification of African economies, their financial development and the quality of their transport and telecommunications infrastructures. Specifically, we find that a substantial improvement in these fundamentals would make intra-African trade significantly income-enhancing.
Keywords: African Research